Keutamaan Menuntut Ilmu pada Puisi Faḍlut-ta’allum: Kajian Antologi Hidāyatul-ażkiyà ilā Ṭarīqil-auliyà Karya Syaikh Zainud-dīn al-Malībārī asy-Syāfi̒ī - Hidayatun Ulfa (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2020)
This study discusses the primacy of the study found in the poems of Faḍlut-Ta’allum in the anthology of the Hidayatul-Ażkiyà ilā Ṭarīqil-Auliyà by Shaykh Zainud-Din al-Malībārī ash-Shāf̒.The analysis in this study refers to the study of semiotics proposed by Riffaterre. Based on the semiotic analysis carried out, it can be concluded that in the poem "Faḍlut-Ta'allum" in the anthology of Hidāyatul-Ażkiyà ilā Ṭarīqil-Auliyà the work of Shaykh Zainud-Din al-Malībārī asy-Syāfi̒ī was found to be unsustainable through the creation of meaning, the form of bahr Kāmil with qafiyyah lamiyyah. As for the semiotic reading it can be seen that the poem is a picture of how the virtues of those who study. By studying, one can get help and ease from God both in the world to the hereafter.